Public Service Management in Higher Education: A Systematic Literature Review - Sukamti, Wahyu; Chown, Dylan (AT-TAJDID: Journal of Islamic Education, 2025)
This article examines public service management in higher education through A Systematic Literature Review (SLR), aiming to identify key aspects, challenges, and strategies in managing public services within universities. The study uses the SLR methodology to systematically gather, evaluate, and synthesize existing research on the topic. A thorough search of academic databases identified studies on service delivery efficiency, student-centered services, leadership, governance, and the integration of technology in university management. The results highlight ongoing challenges such as resource allocation, demographic shifts, and technological adaptation. However, strategies like Total Quality Management (TQM), public-private partnerships, and digital transformation emerge as crucial in enhancing service management. This review’s novelty lies in its comprehensive approach, offering a synthesis of contemporary research on public service management in higher education, and presenting a detailed overview of current models and best practices. The findings of this study offer valuable insights into how institutions can optimize service delivery, improve governance, and better meet the evolving needs of students and stakeholders. By examining these strategies and challenges, this article provides a foundation for further research and practical applications aimed at improving public service management within higher education institutions.